International Legal Regime: Analysis of Cases Relating to Global Terrorism - KALU, Benjamin Okezie; IJIOMAH, Amarachukwu Onyinyechi (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2024)
This paper critically examines the international legal regime addressing global terrorism, with a focus on the judicial decisions that have shaped the scope and enforcement of anti-terrorism laws. It explores the obligations of states under international law to prevent and prosecute terrorism through various legal mechanisms, including domestic laws, treaties, and the exercise of universal jurisdiction. The analysis highlights the role of international courts, including the ICC, ICTY, ICTR, and hybrid tribunals, in addressing terrorism-related crimes. It also delves into the challenges faced by these legal forums, such as jurisdictional immunity and political interference, which hinder effective prosecution. Through a review of landmark cases, the paper demonstrates how terrorism has been defined and prosecuted under International Humanitarian Law (IHL) and International Criminal Law (ICL), providing a comprehensive understanding of how global legal structures work to combat terrorism while addressing the complexities of modern conflicts.